2021
DOI: 10.3390/su13031429
|View full text |Cite
|
Sign up to set email alerts
|

Where to Go with Corporate Sustainability? Opening Paths for Sustainable Businesses through the Collaboration between Universities, Governments, and Organizations

Abstract: This study aims to identify and analyze the Scientific–Technical Scenario on Corporate Sustainability (STS-CS) and propose a Triple Helix-based framework for its development and guidance of future scientific and technological investments. The study was developed using a combined method of bibliometric analysis and content analysis of scientific papers and technical publications (patents, white papers, publications from public bodies, etc.). The scientific papers were searched in the Scopus database and technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 101 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…This answer gives a perception of how this project contributed to improved environmental sustainability, strengthening the arguments that this type of inter-organisational cooperation is seen as a driver to implement sustainable development objectives downstream (Enright et al, 2018;United Nations, 2015) and environmental balance upstream, with universities and research centres being the ideal place to stimulate formation of these partnerships (Nunhes et al, 2020;Perchinunno and Cazzolle, 2020) and others directed towards innovation (Nunhes et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This answer gives a perception of how this project contributed to improved environmental sustainability, strengthening the arguments that this type of inter-organisational cooperation is seen as a driver to implement sustainable development objectives downstream (Enright et al, 2018;United Nations, 2015) and environmental balance upstream, with universities and research centres being the ideal place to stimulate formation of these partnerships (Nunhes et al, 2020;Perchinunno and Cazzolle, 2020) and others directed towards innovation (Nunhes et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…Summarising, it is fundamental to implement partnerships with universities and centres of research and development, technology and sustainable processes, as well as creating programmes with suggested ideas to support the development of socio-environmental projects (Nunhes et al, 2020;Perchinunno and Cazzolle, 2020). In addition, universities can identify recommendations to train professionals able to manage socio-economic questions and implement inter-organisational cooperative relations, directed to innovation and development of sustainable products and processes (Nunhes et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings support the model of a sustainable community based on stakeholder engagement, which can fundamentally change even industrial systems 44 . However, sustainable communities require support from HEIs 26 , which in turn need to connect to the outside world 52 and embrace change, on the basis of dynamic competencies. Some authors have suggested rethinking the role of universities within society 53 by strengthening their connection with local realities in order to increase their resilience 54 , without neglecting the importance of their internalization 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Phase 4 has the content analysis, systematizing the main innovations and governmental, industrial and academic initiatives of the four countries highlighted in STS-S4.0, from the perspective of the TH model. This systematization allows the creation of a framework that contributes to the development of initiatives that combine actions of public and private authorities [50]. Thus, this paper analyzes official documents, such as reports from national and international bodies, government web pages and countries with the highest number of patents related to S4.0.…”
Section: Scientific Methodsmentioning
confidence: 99%